Barómetro de la Innovación 2023 en la Región de Murcia - García Teruel, Pedro Juan; Martínez Solano, Pedro; Sanz Valle, Raquel; Yagüe Guirao, José (EDITUM. Ediciones de la Universidad de Murcia, 2025)
The 2023 innovation barometer studies the situation of the innovative activity of the companies of the Region of Murcia in the 2020-2022 period.With the same methodology as in the previous barometer corresponding to the years 2017-2019, in this study a representative sample of the Murcian business fabric consisting of 265 companies of different sizes and sectors of activity has been interviewed. The presentation of this second barometer is relevant for several reasons: it provides a dynamic perspective of the innovative activity of Murcia companies;It allows monitoring of the effects of public policies to promote past innovation;and helps guide future policies. The results must be analyzed within the context of the exogenous shock that the health crisis derived from the COVID-19 has meant, which also allows to know how the regional business fabric has reacted to this unpublished situation.